Currency Convertibility in the Middle East and North Africa. (International Monetary Fund, 1996)
Currency convertibility is a far-reaching instrument to facilitate integration into the global economy. With it a country can gain the benefits of increased freedom in capital movements and of fostering trade and financial linkages worldwide. A seminar sponsored by the Arab Monetary Fund and the IMF, held in Marrakesh, Morocco, discussed the theoretical and empirical aspects of currency convertibility in the Arab countries. The volume, edited by Manuel Guitian and Saleh M. Nsouli, reproduces the papers presented at the seminar.